1994
DOI: 10.1073/pnas.91.10.4199
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis elongation factor EF-1 alpha expression and longevity in Drosophila melanogaster.

Abstract: It has been proposed that the decline in protein synthesis observed in aging organisms may result from a decrease in elongation factor EF-la. Transgenic Drosophila melanogaster flies carrying an additional copy of the EF-la gene under control of a heat-inducible promoter have an extended lifespan, further indicating that the EF-la gene may play an important role in determining longevity. To test this hypothesis, we have quantitated EF-1amRNA, EF-la protein, and the EF-la complex-formation activity in these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…Elongation factor 1␣ (ef-1␣) plays a role in protein synthesis, which decreases during aging (42). Transgenic flies of overexpressing ef-1␣ were reported to extend lifespan in Drosophila (43), but whether ef-1␣ was overexpressed in these flies is controversial (44). In our screening, the level of ef-1␣ was up-regulated by all three stresses.…”
Section: Figmentioning
confidence: 61%
“…Elongation factor 1␣ (ef-1␣) plays a role in protein synthesis, which decreases during aging (42). Transgenic flies of overexpressing ef-1␣ were reported to extend lifespan in Drosophila (43), but whether ef-1␣ was overexpressed in these flies is controversial (44). In our screening, the level of ef-1␣ was up-regulated by all three stresses.…”
Section: Figmentioning
confidence: 61%
“…Expression was tested using the Si nuclease protection assay described in Shikama et al (1994). Line T was used by Shepherd et al (1989) and has been shown to express the transgenic EF-tz message at 37°C, but not at 29°C (1994).…”
Section: Resultsmentioning
confidence: 99%
“…Independently, Shikama et al (1994) investigated the EF-lcc transgenic flies of Shepherd et a!. (1989) at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Until 1993, these experiments, which were done at two temperatures, 25°C and 29.5°C, were interpreted on the assumption that the gene for elongation factor was more strongly expressed at the higher temperature (a design used to control for position effects). We now know that the additional copy of the gene was not expressed at the temperatures used, neither in Shepherd et al's (1989) experiment (Shikama et al 1994) nor in ours (Kaiser et al, unpubl.). That changed the interpretation of the results from a study of overexpression of a known gene to a study of proper controls in experiments on genetic engineering of phenotypes.…”
mentioning
confidence: 99%
“…Before describing the experiments, we summarize the evidence that the gene was not expressed. Expression was tested using the S 1 nuclease protection assay (Shikama et al 1994). Line T, which was used by Shepherd et al (1989) and which expresses the transgenic EF-lex message at 3rC but not at 29°C (Shikama et al 1994), served as a positive control.…”
mentioning
confidence: 99%